Mapping Analysis of German Language Education Literature Based on Google Scholar and Vosviewer: Bibliometric and Visualization - Hendra, Dani; Achmad, Abdul Kasim (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. This study aims to systematically explore and cluster by mapping and visualizing the german language education research literature. The title and abstract of the article are used to guide the search process by referring to the keyword “german, language, education, german language education”. Found 810 articles that are considered relevant. The study period used as study material is google scholar indexed articles for the last 11 years (2012 to 2022). The results show that research on german language education is separated into 4 terms: german, language, education and german language education with 5 clusters, 2652 links and 9005 total link strength. The term "german" is associated with  98 links with a total link strength of 867 with occurences 184. The term "language" has 97 links with a total link strength of 1018 and occurences 229. The term "education" has 90 links with a total link strength ofhas  1213 and occurences 264. The term “ german language education” has 88 links with a total link strength 478 and occurences 113. The results of the analysis of the german language education in the last 10 years has shown quite frequent fluctuations. In 2012-2013 there’s a significant increased. From 2014-2022 research has significant decreased (sequentially 112, 110, 90, 94, 65, 39, 32, 11 and 5 publications per year ). While the popular german language education research was carried out in 2013, 142 studies. We examined how many articles have been published on german language education and its relation to problem areas using VOSviewer. This review can be a basis for further research. Keywords: Bibliometric, maping analysis, visualizing,  german language education, google scholar, VOSviewer